PESANTREN TANGGUH AS MODERATE ISLAMIC EDUCATION INSTITUTION DURING THE COVID-19 PANDEMIC - Rosidin Rosidin; Syabbul Bachri; Masyithah Mardhatillah; Akhmad Nurul Kawakip; Handoko Ja’far (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
The Covid-19 pandemic divides the attitudes of pesantren residents into three categories: very strict, very loose and moderate (tawassut). This moderate attitude is found in Pesma Al-Hikam and Pesantren Sabilurrosyad in Malang City. This article uses a qualitative approach, then analyzed from the perspective of Pierre Bourdieu’s capital theory. The purpose is to describe how the attitudes, mindset, and residents’ behavior of Pesantren Tangguh related to symbolic, cultural, social, and economic modalities, to control the pandemic crisis. The findings of this article are Pesma Al-Hikam and Pesantren Sabilurrosyad as Pesantren Tangguh are representations of moderate Islamic educational institutions during the Covid-19 pandemic in terms of Bourdieu’s capital theory. First, the nationalist-religious; adaptive and inclusive; and philosophical-rational character in terms of symbolic capital. Second, the theological view that combines destiny and endeavors harmoniously; an elastic and comparative view of Islamic law; and Sufistic behavior that combines ritual and social worship in terms of cultural capital. Third, the behaviour of pesantren residents who remain active in carrying out activities at the pesantren but are disciplined in complying with health protocols in terms of social capital. Fourth, the economic independence of the pesantren in fulfilling the needs and social assistance to the peripheral community in terms of economic capital. In summary, the residents of Pesantren Tangguh show moderate character in aspects of attitude, mindset, and behavior related to symbolic, cultural, social, and economic modalities, enabling the pesantren residents to be able to control the Covid-19 pandemic crisis well.